Tinjauan Yuridis Terhadap Jabatan Menteri Yang Dijabat Oleh Ketua Partai Politik - Grelyano Beryl Mahupale; Salmon Eliazer Marthen Nirahua; Sherlock Halmes Lekipiouw (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The President is assisted by ministers of state who are appointed and dismissed by the President. The Minister is prohibited from holding concurrent positions as the head of an organization that is financed from the State Budget and/or Regional Revenue and Expenditure Budget, while political parties also receive assistance from the APBN. The legal issue is whether the head of a political party can be appointed as a minister, and what are the legal consequences if the head of a political party is appointed as a minister.Purposes of the Research: This study aims to examine and find out whether the position can be held by the chairman of a political party, and to examine and find out the legal consequences of a ministerial position held by the chairman of a political party. Methods of the Research: The type of research used is normative juridical, which is a research that primarily examines legal principles and legal rules using a conceptual approach and legislation, in order to answer the legal issues faced.Results of the Research: The results of the study show that 1) Law No. 2 of 2011 concerning Amendments to Law No. 2 of 2008 concerning Political Parties states that one of the financial sources of political parties is in the form of financial assistance from the APBN/APBD, meanwhile Article 23 letter c of Law The Law of the Republic of Indonesia Number 39 of 2008 concerning State Ministries also stipulates that the Minister is prohibited from holding concurrent positions as: the head of an organization financed from the State Budget and/or Regional Revenue and Expenditure Budget. thus, the Chairperson of a Political Party cannot become a minister. 2) The legal consequence is that the chairman of the Golkar political party as one of the ministers in the current cabinet of President Joko Widodo must be dismissed from his position as minister.